Mitreola sinhoensis (Loganiaceae), a new species from northwestern Vietnam - Tran, Thi Phuong Anh; Nguyen, Khang Sinh; Quang, Bui Hong; Bui, van Thanh; Trung, Nguyen Thi; Binh, Tran Duc; Nguyen, Thi Thanh; Wu, Lei (Phytotaxa, 2025)
Mitreola sinhoensis, a new species of Loganiaceae, is described and illustrated. It was found on limestone mountain in Sin Ho Commune, Lai Chau Province, northwestern Vietnam. The new species is characterized by conspicuously elongated stems, a fibrous root system with 1–3 well-developed roots distinct from the others, narrowly lanceolate to linear-lanceolate leaf blade 2.5–4.5 × 0.3–0.6 cm with attenuate base and apex, terminal cymes typically bearing seven flowers, oblong corolla lobes, stamens inserted at the lower one-third of the corolla tube, widely elliptic to subrounded anthers, and puberulent capsule distally bilobed for more than half of its total length. In addition, the morphological description, brief data on its distribution, habitat, and conservation status are provided. Its taxonomic relationships with other species of Mitreola possessing conspicuously elongated stems and narrow leaves are also discussed.